Planetary pictures: historicizing environmental and climate sciences in the Anthropocene - Thomas Simpson; James Poskett (BJHS Themes)
How should historians of environmental and climate sciences respond to the Earth's move from the blank canvas to a foreground feature of ‘big-picture’ scholarship? This article highlights three crucial themes for histories of science in the Anthropocene: categories of scale and methods of scaling, the relationship between history of science and the disciplines it historicizes, and the entanglement of environmental damage and environmental knowledge. Critically engaging a wide range of recent literature across history of science, environmental history, and environmental humanities, alongside an array of case studies, the article puts forward an agenda for ‘planetary pictures’. These are analyses that actively contribute to the vital political and ethical task to make visible, and force a reckoning with, the perpetrators and victims of Anthropocene violence.